Some comments about the medical record - Alfredo Darío Espinosa Brito (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Some issues are commented about the medical records at present. There are included aspects as: history, importance, how to teach its performance, different functions, types of medical charts, and individual and institutional responsabilities with this document.